Lifestyle Medicine Shared Medical Appointments. Issue 1 (January 2021) - Lacagnina, Salvatore; Tips, Jean; Pauly, Kaitlyn; Cara, Kelly; Karlsen, Micaela
Chronic diseases pose many challenges to health care providers and the health care system from a human capital, logistic, and financial perspective. To overcome these challenges, efficient and effective health care delivery models that address multiple chronic conditions need to be leveraged. Shared medical appointments are one potential solution to address these issues. This article offers a brief history of group visits and shared medical appointments and reviews the available data regarding their outcomes. It describes the benefits of using lifestyle medicine as the primary therapeutic modality within a shared medical appointment to treat, reverse, and prevent chronic disease. Key considerations and action steps for the implementation of lifestyle medicine shared medical appointments (LMSMAs) are outlined and the potential delivery of these services via telehealth is explored.